Case Report: Pancreatic metastasis of renal cell carcinoma 16 years after nephrectomy - Lou, Yidan; Guo, Kaibo; Zheng, Song (Frontiers in Oncology, 2023)
Background Renal cell carcinoma (RCC) is the most common renal malignancy, and may metastasize to different sites in the body via hematogenous and lymphomatous routes. The pancreas is a rare metastatic site of metastatic RCC (mRCC) and isolated pancreatic metastasis of RCC (isPMRCC) is even rarer. Results The present report describes a case of isPMRCC that recurred 16 years after surgery. The patient responded well to the treatment with pancreaticoduodenectomy and systemic therapy, and no recurrence was recorded after 2 years. Conclusions isPMRCC is a distinct subgroup of RCC with unique clinical characteristics that may be explained by its underlying molecular mechanisms. Surgery and systemic therapy confer survival benefits to patients with isPMRCCs, although the recurrence problem has to be paid attention to.